2014
DOI: 10.4184/asj.2014.8.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Ossification of the Ligamentum Flavum

Abstract: Ossification of the ligamentum flavum is a rare cause of thoracic myelopathy. It develops in East Asians more frequently than in people from other areas. The exact pathophysiology has not been elucidated yet; however, it largely depends on biomechanical alterations, especially changes in the tensile force. Because the spinal cord is compressed from the posterior side, the first and most common clinical manifestation is usually loss of functional gait and spastic paralysis, which develop as the spinal cord comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 41 publications
2
98
0
Order By: Relevance
“…Many studies have demonstrated the critical role of mechanical stress in the development of TOLF (7,15,2225). We previously reported that mechanical stress induced the osteogenic differentiation of ligament cells derived from patients with TOLF, which in turn promoted OLF, leading us to conclude that stress facilitated, but did not initiate the development of TOLF (10).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the critical role of mechanical stress in the development of TOLF (7,15,2225). We previously reported that mechanical stress induced the osteogenic differentiation of ligament cells derived from patients with TOLF, which in turn promoted OLF, leading us to conclude that stress facilitated, but did not initiate the development of TOLF (10).…”
Section: Discussionmentioning
confidence: 99%
“…However, other techniques such as fenestration, laminoplasty, and hemilaminectomy have been reported as well. 914 Even with successful surgical decompression, there can be marked variation in clinical outcomes and the incidence of postoperative complications is not infrequent. 9,11,1417 …”
mentioning
confidence: 99%
“…Imaging in these cases did not show any recurrences of spinal cord compression, and there were no indications for reoperation of the cervical spine. The exact cause was uncertain; however, long-term duration of CSM symptoms and low preoperative JOA scores might have been the main reasons [20]. Previous literatures had reported that degeneration spine disease might contribute to the decrease of cervical ROM and lordosis as measured by CCI [13,21].…”
Section: Discussionmentioning
confidence: 97%